SYNERGY AND COLLABORATION BETWEEN GOVERNMENT AND PRIVATE INSTITUTIONS IN BUILDING HALAL ECOSYSTEMS IN INDONESIA - Rachman, Abdul; Sangare, Bilaly (Islam Futura, 2023)
This study aims to analyze and criticize the synergy and collaboration of government agencies and private institutions such as universities, social organizations, educational foundations, and others in building a halal ecosystem through the free halal certification program (SEHATI) with the Self Declare pathway. The implementation of halal certification involves many parties and government agencies because it relates to regulations, budgets, and others. Therefore, there needs to be cross-sectoral synergy and collaboration between ministries, local governments, and the private sector in accelerating the development of the halal ecosystem in Indonesia. This research method uses descriptive qualitative with a normative juridical approach. Data collection was carried out by observation and in-depth interviews with institutions participating in the free and regular halal certification program. The results of this study illustrate that in implementing halal certification, BPJPH as an institution that has the authority according to the mandate of the law has a big role in implementing halal certification in Indonesia. However, in practice, the BPJPH institution synergizes and collaborates more with private institutions such as universities, educational foundations, community organizations (ormas), and associations, compared to cross-sectoral fellow government agencies and local governments in the halal certification program.